Intraoperative Surgeon-Performed versus Conventional Anesthesiologist-Performed Continuous Adductor Canal Block in Total Knee Arthroplasty: A Randomized Controlled Trial - Chaiperm, Chayut; Tanavalee, Chotetawan; Kampitak, Wirinaree; Amarase, Chavarin; Ngarmukos, Srihatach; Tanavalee, Aree (The Journal of Knee Surgery, 2023)
A continuous adductor canal block (cACB) for pain control in total knee arthroplasty (TKA) is always performed by an anesthesiologist. A surgeon-performed cACB during surgery is somewhat questionable in terms of feasibility, reproducibility, and efficacy. This study was divided into two phases. In Phase 1 study, an experimental dissection of 16 cadaveric knees to expose the saphenous nerve and related muscles around the adductor canal was conducted. The extent of dye after injection via a catheter inserted into the adductor canal at the time of TKA was evaluated. In Phase II, a randomized controlled trial study comparing clinical outcomes between surgeon-performed (Group 1) and anesthesiologist-performed cACB (Group 2) during TKA in 63 patients was evaluated. The visual analogue scale (VAS) at rest and during movement at several time points and functional outcomes during hospitalization were compared. The Phase I study demonstrated surgeon-performed cACB during surgery feasible and reproducible with consistent dye extension into the adductor canal after injection via a catheter. In the Phase II study, 29 patients of Group 1 and 30 patients of Group 2 completed the evaluation with no differences in baseline parameters. The VAS during movement at 24 and 36 hours, quadriceps strength, time up and go test, and knee motion at different time points, and total morphine consumption showed no differences between both groups. There were no procedure-related complications. The surgeon-performed cACB during surgery was feasible and reproducible with similar VAS scores and functional outcomes during hospitalization to anesthesiologist cACB. Level of evidence is Level I, prospective randomized trial.
Keywords: adductor canal block; peripheral nerve block; total knee arthroplasty; surgeon-performed ACB